Peer-To-Peer Lenders and Banks: Compete or Complement? A Position Paper - Jul Aidil Fadli (SAFE-Network, 2022)
This paper is a position paper that aims to identify whether the presence of P2P lending is a problem for banking companies or vice versa. We answer this question through three approaches: in terms of business models, SWOT analysis, the risks faced by them, and market segmentation. Our identification shows that due to its easy communication channel (the Internet) and affordable infrastructure, P2P lenders are a competitive rival. P2P lenders should move to a niche market that is still available, namely SME financing. These SMEs are then expected to become more mature and bankable so that they can get financing from banks to grow bigger. They have qualified capabilities for this segment and capable technology. This could be their competitive advantage over banks. Banks operate in safe segments for them to avoid bank panics, bank runs, and economic instability. Meanwhile, banks can engage in other market segments, such as housing finance, commercial, and corporate financing. This synergy will have a harmonious impact on economic progress.